(untitled) (Research, Society and Development, 2023)
Bentonites are clayey materials composed mainly of montmorillonite (a mineral from the smectite group). Their characteristic colloidal composition determines the incorporation of water, forming plastic pastes. Whether sodium or calcium, the bentonites are widely used in numerous industrial applications due to their structural characteristics, availability and abundance in nature, and low cost. The present work aimed to carry out a brief narrative literature review on the potential of bentonite clays regarding their characteristics and some applications. Articles were selected between the years 2017 to 2022 from the Science Direct platform and using the following keywords: bentonite, environmental remediation, cosmetics and pharmaceuticals, biomedicine, and civil construction. The results showed that the most studied area of application was that of environmental remediation connected to investigations in adsorption, which demonstrates the high interest and motivation of researchers in themes related to sustainability. Therefore, it is expected that this preliminary reading can contribute to the understanding of the technological potential of bentonite, bringing clarity to the study of its properties and applications.